Physicochemical and Sensory Evaluation of Yanggaeng Treated with Roasted Guatemalan Coffee Extracts - Jisu Lee; Inyong Kim; Hyunsoo Jang; Yeon-Woo Kim; Minseo Cho; Jiwoo Lee; Jaewook Do; Caglar Doguer; Miae Doo; Jung-Heun Ha (Applied Sciences)
This study evaluated the effects of Guatemalan coffee extract (G) on the physicochemical, antioxidant, and sensory properties of Yanggaeng at different roasting levels (light, medium, and dark) and concentrations (0%, control group [CON]; 2%, 2; 4%, 4; and 6%, 6). Moisture, ash, fat, protein, and carbohydrate contents varied significantly with G concentration and roasting level, with light roasts exhibiting the highest moisture and fat content, but the lowest ash and carbohydrate content. Colorimetric properties showed a dose-dependent decrease in lightness and an increase in redness and yellowness with the addition of G. Additionally, pH levels increased in light and dark roasts, but decreased in medium roasts, whereas Brix values increased with G, peaking in dark roasts. Antioxidant activity, assessed by total phenolic content and 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging, improved notably in the medium and dark roasts. Textural properties including hardness, resilience, and chewiness also benefited from the addition of G. Sensory evaluations favored Yanggaeng containing 4–6% G, especially in dark roasts, for attributes such as color, scent, and overall taste. Dark roast concentrations of 4% and 6% were identified as optimal for enhancing the properties of Yanggaeng, supporting the potential of G to develop innovative high-quality desserts tailored to modern consumer preferences.